Metabolic bone disease of prematurity: causes, recognition, prevention, treatment and long-term consequences. Issue 5 (11th May 2019) - Chinoy, Amish; Mughal, Mohamed Zulf; Padidela, Raja
Abstract : Metabolic bone disease of prematurity (MBDP) is characterised by skeletal demineralisation, and in severe cases it can result in fragility fractures of long bones and ribs during routine handling. MBDP arises from prenatal and postnatal factors. Infants who are born preterm are deprived of fetal mineral accumulation, 80% of which occurs in the third trimester. Postnatally, it is difficult to maintain a comparable intake of minerals, and medications, such as corticosteroids and diuretic therapy, lead to bone resorption. With improvements in neonatal care and nutrition, the incidence of MBDP in preterm infants appears to have decreased, although the recent practice of administering phosphate supplements alone will result in secondary hyperparathyroidism and associated bone loss, worsening MBDP. Postnatal immobilisation and loss of placental supply of oestrogen also contribute to skeletal demineralisation. There is no single diagnostic or screening test for MBDP, with pitfalls existing for most radiological and biochemical investigations. By reviewing the pathophysiology of calcium and phosphate homeostasis, one can establish that plasma parathyroid hormone is important in determining the aetiology of MBDP – primarily calcipaenia or phosphopaenia. This will then direct treatment with the appropriate supplements while considering optimal physiological calcium to phosphate ratios.